Bibliometric Analysis and Visualization of Research in the Field of Green Economy (1993-2023) - Melike Torun (İktisat Politikası Araştırmaları Dergisi)
Based on the data of articles indexed in the Web of Science Core Collection database between 1993 and 2023, this research intends to add to the body of literature by gaining an understanding of the development trend of popular scientific studies on the green economy. The bibliometric analysis method VOS Viewer is used to statistically assess the keywordsand highly cited countries in this topic for this purpose. The study’s analysis includes two map-based visualizations, one of which shows themost often cited countries and the other depicts the trending keywords over time.